To solve the equation \(10x - 12 - 8x = 4x + 15\), we can follow these two steps:
Step 1: Combine like terms on the left side of the equation.
Starting with: \[ 10x - 12 - 8x = 4x + 15 \]
Combine \(10x\) and \(-8x\): \[ (10x - 8x) - 12 = 4x + 15 \] Which simplifies to: \[ 2x - 12 = 4x + 15 \]
Step 2: Move all terms involving \(x\) to one side and constant terms to the other side.
Subtract \(4x\) from both sides: \[ 2x - 4x - 12 = 15 \] Which simplifies to: \[ -2x - 12 = 15 \]
Now, we can move \( -12 \) to the right side by adding \(12\) to both sides: \[ -2x = 15 + 12 \] \[ -2x = 27 \]
Now the equation can be further simplified to get \(x\) alone: Divide both sides by \(-2\): \[ x = -\frac{27}{2} \]
Now we have the equation in \(x = a\) format, where \(a = -\frac{27}{2}\).